Novel Pathogenic Mutation Mapping of ASPM Gene in Consanguineous Pakistani Families with Primary Microcephaly - Batool,T. (2023)
Abstract Autosomal recessive primary microcephaly (MCPH) is a neurodevelopmental disorder characterized by a congenitally reduced head circumference (-3 to -5 SD) and non-progressive intellectual disability. The objective of the study was to evaluate pathogenic mutations in the ASPM gene to understand etiology and molecular mechanism of primary microcephaly. Blood samples were collected from various families across different remote areas of Pakistan from February 2017 to May 2019 who were identified to be affected with primary microcephaly. DNA extraction was performed using the salting-out method; the quality and quantity of DNA were evaluated using spectrophotometry and 1% agarose gel electrophoresis, respectively in University of the Punjab. Mutation analysis was performed by whole exome sequencing from the Cologne Center for Genomics, University of Cologne. Sanger sequencing was done in University of the Punjab to confirm the pathogenic nature of mutation. A novel 4-bp deletion mutation c.3877_3880delGAGA was detected in exon 17 of the ASPM gene in two primary microcephaly affected families (A and B), which resulted in a frame shift mutation in the gene followed by truncated protein synthesis (p.Glu1293Lysfs*10), as well as the loss of the calmodulin-binding IQ domain and the Armadillo-like domain in the ASPM protein. Using the in-silico tools Mutation Taster, PROVEAN, and PolyPhen, the pathogenic effect of this novel mutation was tested; it was predicted to be “disease causing,” with high pathogenicity scores. One previously reported mutation in exon 24 (c.9730C>T) of the ASPM gene resulting in protein truncation (p.Arg3244*) was also observed in family C. Mutations in the ASPM gene are the most common cause of MCPH in most cases. Therefore, enrolling additional affected families from remote areas of Pakistan would help in identifying or mapping novel mutations in the ASPM gene of primary microcephaly.